(878) العمالة في صناعة الغزل والنسيج Workforce in Textile Industry. - حسان, محمد محمد (معهد التخطيط القومي, 2025)
يعتمد الاعتماد على التعداد العام للسكان كمصدر رئيسي لدراسة العمالة في مختلف الأنشطة الاقتصادية على عدم تحقيق دراسة واقعية تعكس حالة القوى العاملة بمستوياتها ومهاراتها المختلفة. لذا، من الضروري إجراء دراسات قطاعية تفصيلية عن العمالة المتاحة، تشمل التخصصات والمهارات ومستويات التعليم، للحصول على مؤشرات دقيقة تصحح البيانات المعتمدة على التعداد العام. بدأت الدراسة في قطاع الغزل والنسيج، الذي يتميز بالاستقرار والتقدم الصناعي، وستتبعها دراسات لقطاعات أخرى. يشمل قطاع الغزل والنسيج الأنشطة التالية: غزل ونسج القطن، صباغة وتجهيز القطن، الصوف، الألياف الصناعية، الألياف الطبيعية، التريكو، والخدمات. Relying on the general population census as the main source for studying labor in various economic activities does not lead to a realistic study that accurately reflects the workforce's levels and skills. Therefore, it is essential to conduct sectoral studies detailing the available labor, including specialties, skills, and educational levels, to obtain accurate indicators that correct the data based on the census. The study began with the spinning and weaving sector, known for its stability and industrial advancement, and will be followed by studies of other sectors. The spinning and weaving sector includes the following activities: cotton spinning and weaving, cotton dyeing and finishing, wool, synthetic fibers, natural fibers, knitting, and services.